Combined treatment of a medulla oblongata hemangioblastoma via permanent cysto-cisternal drainage and (postponed) gamma knife radiosurgery: a case report and review of the literature. (4th May 2022) - Bartoš, Robert; Lodin, Jan; Marek, Tomas; Sameš, Martin; Němcová, Veronika; Liščák, Roman
Abstract: Background: Hemangioblastomas are histologically benign tumors with a variable degree of morbidity and mortality based on various factors, including their anatomical location. The following paper illustrates a unique approach of combined therapy of a brainstem hemangioblastoma (HB) not associated with von Hippel-Lindau disease (vHLd) located in the medulla oblongata. Case description: A 21-year-old preschool teacher presented with vertigo, followed by dysphagia, trouble coughing, tongue paresis and headache and vomiting. Magnetic resonance imaging (MRI) revealed a large cystic lesion with a small intramural nodule located in the left anterolateral medulla oblongata directly behind the vertebral artery. The diagnosis of hemangioblastoma was supported by digital subtraction angiography. Conclusion: Combined therapy consisted primarily of acute surgical fenestration and permanent drainage of the cystic portion of the tumor, due to symptomatic expansion. Follow-up stereotactic gamma knife radiosurgery was performed after 2 years for minor progression of the tumor nodule. To the best of our knowledge, this is the first time such approach has been described in the literature for this pathology.